Occupational Stress and Catholic Priests: A Scoping Review of the Literature - Ruiz-Prada, Miguel (Journal of religion and health, 2021)
This study offers an exploratory review of the experience of stress and burnout syndrome among Catholic priests. Following Arksey and O’Malley's (Int J Soc Res Methodol 8(1):19-32, 2005, https://doi.org/10.1080/1364557032000119616) protocol, a scoping study was conducted. Given the scarcity of studies found on the subject, a broad selection criterion was used, which included quantitative, qualitative and mixed studies, literature reviews and comparative studies with other professions. The results reveal various risk factors: work overload among younger generations of priests, a sociocultural context that distrusts the clergy, neurotic, introverted, perfectionist and narcissistic personality styles, avoidant and complacent coping styles, living alone, not having sufficient support (especially from the Church authorities), excessive demands and lack of boundaries related to the priestly role and submissive obedience styles, among others. However, the studies reviewed also identified important protection factors: promoting optimism, an approach-based coping style and a collaborative way of resolving conflicts, frequent physical exercise, eating a balanced diet, finding time to rest, strengthening personal identity, social support (from parishioners, collaborators, colleagues, superiors) and leading an active spiritual life. Stress and burnout are associated with certain pathologies linked to smoking, alcoholism, obesity, diabetes, cardiovascular disease, anxiety and depression. Strengthening protective factors and minimizing the impact of risk factors would do much to improve the clergy’s occupational health.